2015
DOI: 10.1016/j.nlm.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the nucleus reuniens/rhomboid causes a delay-dependent impairment of spatial working memory

Abstract: Inactivation of the rodent medial prefrontal cortex (mPFC) and hippocampus or disconnection of the hippocampus from the mPFC produces deficits in spatial working memory tasks. Previous studies have shown that delay length determines the extent to which mPFC and hippocampus functionally interact, with both structures being necessary for tasks with longer delays and either structure being sufficient for tasks with shorter delays. In addition, inactivation of the nucleus reuniens (Re) / rhomboid nucleus (Rh) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 47 publications
7
55
1
Order By: Relevance
“…A growing number of behavioural studies has provided evidence that RE is indeed involved in cognitive functions, most likely by coordinating neuronal activities in hippocampus and mPFC (Dolleman-van der Weel et al, 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Loureiro et al 2012;Prasad et al 2012;Cholvin et al 2013;Hallock et al 2013;Xu and Sűdhof 2013;Saalmann 2014;Bobal and Savage 2015;Ito et al 2015;Layfield et al 2015;Prasad et al 2016). Because mPFC lacks a direct return projection to the hippocampus (Sesack et al 1989;Jay and Witter 1991), RE might relay mPFC-processed information back to the hippocampus as part of a closed CA1-mPFC-RE-CA1 circuit Xu and Sűdhof 2013).…”
Section: Functional Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of behavioural studies has provided evidence that RE is indeed involved in cognitive functions, most likely by coordinating neuronal activities in hippocampus and mPFC (Dolleman-van der Weel et al, 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Loureiro et al 2012;Prasad et al 2012;Cholvin et al 2013;Hallock et al 2013;Xu and Sűdhof 2013;Saalmann 2014;Bobal and Savage 2015;Ito et al 2015;Layfield et al 2015;Prasad et al 2016). Because mPFC lacks a direct return projection to the hippocampus (Sesack et al 1989;Jay and Witter 1991), RE might relay mPFC-processed information back to the hippocampus as part of a closed CA1-mPFC-RE-CA1 circuit Xu and Sűdhof 2013).…”
Section: Functional Relevancementioning
confidence: 99%
“…Recent studies have indicated the importance of RE for cognitive processes, such as behavioural flexibility, strategy shifting, inhibitory response control, associative learning, memory consolidation, working memory, fear memory, memory generalization, goal-directed navigation, and executive behaviours (Dollemanvan der Weel et al 2009;Davoodi et al 2011;Eleore et al 2011;Hembrook et al 2011;Kincheski et al 2012;Loureiro et al 2012;Cholvin et al 2013;Hallock et al 2013;Prasad et al 2013;Varela et al 2013;Wheeler et al 2013;Xu and Sűdhof 2013;Duan et al 2015;Griffin 2015;Ito et al 2015;Layfield et al 2015;Anderson et al 2015;Prasad et al 2016). This variety of memory-related behaviours has also been associated with the interplay between the medial prefrontal cortex (mPFC) and the hippocampus (Jin and Maren 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Inactivation of RE/RH, the hippocampus or the mPFC impaired the shift to a place response, indicating that disruption of the HF, the mPFC, or the RE-mediated communication between them altered performance on this spatial WM task. Finally, Layfield et al (2015) recently reported that suppression of RE/RH did not disrupt performance on continuous version of a T-maze alternation task, which appears to depend on the mPFC, but significantly altered performance on the delayed version of the task which reportedly enlists both the HF and the mPFC (Aggelton et al, 1986; Brito and Brito, 1990; Sanchez-Santad et al, 1997; Hock and Bunsey, 1998; Lee and Kesner, 2003; Yoon et al, 2008). …”
Section: Introductionmentioning
confidence: 96%
“…Based on these patterns of connections, several recent behavioral studies have examined the role of RE (and the dorsally adjacent rhomboid nucleus, RH) in various spatial working memory tasks (Hembrook and Mair, 2011; Hembrook et al, 2012; Loureiro et al, 2012; Cholvin et al, 2013; Hallock et al, 2013; Layfield et al, 2015). The general conclusion from these studies is that RE/RH is most directly involved in those tasks that involve the cooperative actions of the mPFC and the hippocampus (for review, Cassel et al, 2013; Vertes et al 2015; Griffin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We compared experimental and control rats on operant behavioral tasks assessing visual attention and working memory, associative learning and decision-making. We also tested rats on a radial arm maze as several studies indicate a role for the NRe in spatial memory (Hembrook and Mair, 2011; Loureiro et al, 2012; Layfield et al, 2015; Ito et al, 2015). We report several features that distinguish NRe lesions from those of its projection targets.…”
mentioning
confidence: 99%